2003
DOI: 10.1152/ajprenal.00143.2003
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal ENaC subunit and sodium transporter abundances in streptozotocin-induced type 1 diabetes

Abstract: Uncontrolled diabetes mellitus (DM) is associated with copious water and sodium losses. We hypothesized that the kidney compensates for these losses by increasing the abundances of key sodium and water transporters and channels. Using targeted proteomic analysis via immunoblotting of kidney homogenates, we examined comprehensive regulation of transport proteins. In three studies, streptozotocin (STZ; 65 mg/kg) or vehicle was administered intraperitoneally to male Sprague-Dawley rats. In study 2, to control for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 31 publications
7
42
1
Order By: Relevance
“…Similarly, E 2 replacement normalized the expression of ␣-and ␤-ENaC, which were reduced in diabetic female rats. Decreased ␣-and ␤-ENaC in the chronically diabetic female rats contrasted with our earlier finding in male rats, which were diabetic for only 4 days (142). The reasons underlying these discrepancies are not clear.…”
Section: Altered Expression Of Sodium Transporter and Channels In Diacontrasting
confidence: 98%
See 1 more Smart Citation
“…Similarly, E 2 replacement normalized the expression of ␣-and ␤-ENaC, which were reduced in diabetic female rats. Decreased ␣-and ␤-ENaC in the chronically diabetic female rats contrasted with our earlier finding in male rats, which were diabetic for only 4 days (142). The reasons underlying these discrepancies are not clear.…”
Section: Altered Expression Of Sodium Transporter and Channels In Diacontrasting
confidence: 98%
“…E 2 replacement in STZ-diabetic rats altered the ratio of estrogen receptor subtypes in the kidney (164) and also attenuated the severity of the diabetes, as measured by a reduction in the hyperglycemia in these rats (124). With regard to changes in transport proteins, NKCC2 abundance was increased by diabetes in the whole kidney and outer medulla, as in our earlier short-term (4-day) study previously described (142). E 2 replacement normalized NKCC2 expression.…”
Section: Altered Expression Of Sodium Transporter and Channels In Diasupporting
confidence: 66%
“…It is, thus, unlikely that the increase in HSP expression we observed in the diabetic outer medulla was secondary to STZ-induced tubular injury. In both human and experimental diabetes, there is a reduction in oxygen tension, particularly in the outer medulla, and overexpression of tubular carrier proteins in outer medullary thick ascending limbs, which enhance sodium chloride reabsorption and interstitial osmolarity (11,33). The increased hypertonic and hypoxic stress in the diabetic outer medulla may induce an overexpression of HSP localized specifically to this area, which, in turn, may result in cytoprotection and counterbalance diabetes-induced cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations of NCC (Gitelman syndrome) cause renal salt wasting with hypotension, hypokalemic alkalosis, and hypocalciuria, 3 whereas increased NCC activity because of mutations within the NCC-regulating with-no-lysine kinase 1 (WNK1) or WNK4 (familial hyperkalemic hypertension) are associated with severe salt-sensitive hypertension, hyperkalemia, metabolic acidosis, and hypercalciuria. 4 Increased NCC expression has been linked to renal Na + retention in liver cirrhosis, 5 diabetes mellitus, 6 b-adrenergic stimulation, 7 and immunosuppressive treatment. 8 The clinical significance of the DCT is also emphasized by clinical trials that confirmed the DCT as an important target for antihypertensive therapy.…”
mentioning
confidence: 99%